2021
DOI: 10.1007/s00702-021-02364-6
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to dissect a peripheral marker based on cell pathology in Parkinson's disease

Abstract: Peripheral markers in Parkinson’s disease (PD) represent a hot issue to provide early diagnosis and assess disease progression. The gold standard marker of PD should feature the same reliability as the pathogenic alteration, which produces the disease itself. PD is foremost a movement disorder produced by a loss of nigrostriatal dopamine innervation, in which striatal dopamine terminals are always markedly reduced in PD patients to an extent, which never overlaps with controls. Similarly, a reliable marker of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…The reduction of these genes from initial pathway complexes suggests a decrease in the formation of the autophagosome vesicles that surround the substrate. Recently, an ultrastructural study in PBMCs obtained from PD patients demonstrated fewer autophagy vacuoles per cell, supporting our results 96 . In particular, we found that the reduction of BECLIN1 and ATG5 in PBMCs of PD patients was aligned with the significant reduction in transcriptional levels of Atg5 and a tendency in Beclin1 in murine macrophages treated with α-synuclein.…”
Section: Discussionsupporting
confidence: 90%
“…The reduction of these genes from initial pathway complexes suggests a decrease in the formation of the autophagosome vesicles that surround the substrate. Recently, an ultrastructural study in PBMCs obtained from PD patients demonstrated fewer autophagy vacuoles per cell, supporting our results 96 . In particular, we found that the reduction of BECLIN1 and ATG5 in PBMCs of PD patients was aligned with the significant reduction in transcriptional levels of Atg5 and a tendency in Beclin1 in murine macrophages treated with α-synuclein.…”
Section: Discussionsupporting
confidence: 90%
“…LC3-I to LC3-II conversion is elevated in PBMCs [24], and LC3 gene expression as well as LC3-II protein levels are significantly increased in the leukocytes of PD patients, indicating autophagosome accumulation [6]. On the other hand, the number of autophagy vacuoles per cell in PBMC of PD patients is decreased compared with healthy subjects [57]. The modulation of intracellular signaling implicated in neuronal cell survival, growth, proliferation, and metabolism in PD indicates that p62-involved autophagy activity is regulated at posttranslational and transcriptional levels [58].…”
Section: Discussionmentioning
confidence: 95%
“…Transmission election microscopy (TEM) is a gold standard to assess the status of autophagy. Recently, it has been successfully applied to analyze peripheral autophagy markers associated with PD 96 . TEM is recommended to be used to evaluate the efficacy of the screened receptors and modulators and investigate their functional implications for autophagy.…”
Section: Screening For Selective Autophagy Receptors and Modulatorsmentioning
confidence: 99%